Escape from Kantian Eurocentric bias in cross-cultural psychology. (December 2020) - Hwang, Kwang-Kuo
Taking Kant's misjudgment on Confucian silver rule as the point for first cut, this article is designated to illustrate the fallacy of imposed Orientalism prevailing in mainstream cross-cultural psychology which tends to understand non-Western cultures by a mental set of dualism with a tendency of Westcentrism, particularly the popular research on individualism-collectivism. This type of Euro-centric or Westcentric misjudgments are very common in Western social sciences, for instance, Confucian ethics are frequently described as particularistic in consideration of the distinction between universalism and particularism made byParsons . In order to help the international academic community to escape from the trap of Eurocentric bias, this article will argue for and illustrate its characteristic of contextualized universalism step by step on the basis ofHwang's previous research. Finally, the meaning of constructing scientific microworld of Confucian ethics will be discussed to explain how Chinese people are facing the impact of Western cultured during the globalization age of multiculturalism.